Evaluating the level and nature of sustainable development of a mining operation: a new approach using the ideas of coupled environment?human systems. (21st December 2010) - Phillips, Jason
Sustainable mining is a key goal of the mining industry in order to address the associated impacts of mining. However, there have been challenges in implementing often confused and conflicting anthropocentric definitions of sustainable development. Consequently, this paper presents the application of a mathematical model of sustainable development to a quantitatively-based Environmental Impact Assessment (EIA) for a mining operation in India. The results indicated the proposed project with an Environmental Management Plan achieved a SEc -value of 0.423, compared to the baseline SEc -value of 0.425. These scores indicated weak ecological sustainable development.